2014
DOI: 10.1177/0013124514529327
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Physical Education Teachers’ Experiences in Teaching English Language Learners

Abstract: The purpose of the current study was to describe and explain the views on teaching English Language Learners (ELLs) held by six elementary physical education (PE) teachers in the Midwest region of the United States. Situated in positioning theory, the research approach was descriptive–qualitative. The primary sources of data were face-to-face interviews, and the transcript data were analyzed using NVivo 8 software and constant comparative method. The recurrent themes that emerged from the data were as follows:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Since it was launched in the 1990s, the European Commission and the Council of Europe have funded many initiatives in support of CLIL because it responded to a need in Europe for enhancing second-language education and bilingualism (Marsh, 2002). In the Physical Education (PE) field it is easy to encounter examples of its application in countries such as Italy, Greece or Spain among others (Salvador et al, 2017) and even similar studies which use PE to teach a second language have been developed in the USA (Lieberman et al, 2010;Nguyen & Watanabe, 2013;Santillan, Jacobs & Wright;2015;Sato & Hodge;Sato, Walton & Kim, 2017), even though these do not use CLIL methodology. Specifically, the focus setting of the current paper is the Spanish context, although some of the results presented may be interesting for the rest of countries using CLIL and/or those interested in using it or a similar method in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was launched in the 1990s, the European Commission and the Council of Europe have funded many initiatives in support of CLIL because it responded to a need in Europe for enhancing second-language education and bilingualism (Marsh, 2002). In the Physical Education (PE) field it is easy to encounter examples of its application in countries such as Italy, Greece or Spain among others (Salvador et al, 2017) and even similar studies which use PE to teach a second language have been developed in the USA (Lieberman et al, 2010;Nguyen & Watanabe, 2013;Santillan, Jacobs & Wright;2015;Sato & Hodge;Sato, Walton & Kim, 2017), even though these do not use CLIL methodology. Specifically, the focus setting of the current paper is the Spanish context, although some of the results presented may be interesting for the rest of countries using CLIL and/or those interested in using it or a similar method in the future.…”
Section: Introductionmentioning
confidence: 99%
“…referred to group separateness between students with and without disadvantages) (Place and Hodge, 2001). Therefore, many ELLs could not minimize gaps in their linguistic competence, understand the meaning of lessons and practices, and switch or translate between new and past PE discourse through interacting with local students (Norris and Ortega, 2006;Sato and Hodge, 2016). Miller (2010) asserted that "if students cannot be heard representing themselves and enacting of exclusion from social interaction seems inevitable" (p.73).…”
Section: Discussionmentioning
confidence: 99%
“…When PE teachers educate students with diverse backgrounds, some struggle to modify the curriculum and find relevant pedagogy related to language and cultural relations (Knop et al, 2001). For example, Sato and Hodge (2016) studied six elementary PE teachers' initial experiences and challenges in teaching newly coming ELLs in American public schools. They found that the six PE teachers encountered numerous challenges when teaching elementary-aged ELLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mainstream context, ELLs are often positioned as (non‐White) immigrants and stereotyped based on their ethnicity, race, religion, or culture (Hanassab, ). In some classrooms, they are treated as uninvited guests or as invisible students who are less competent than their local, native peers (Sato & Hodge, ; Sato, Walton‐Fisette, & Kim, ; Yoon, , ) or who lack the language skills and necessary knowledge about the U.S. education system (Page, ). This deficit learner approach creates a false image that ELLs lack the ability for critical engagement (Harklau, ; Rubinstein‐Ávila, ), with the excuse that ELLs are still in the process of language acquisition (Park, ), so engaging in such linguistically demanding practices would be too challenging (Lee & Runyan, ).…”
Section: Rationale Of the Studymentioning
confidence: 99%